ARRIVAL DIRECTION OF AURORAL HISS EMISSIONS DETERMINED BY TRIPARTITE OBSERVATION - ナガタ, タケシ; ヒラサワ, タケオ; ニシノ, マサノリ; NAGATA, Takesi; HIRASAWA, Takeo; NISHINO, Masanori (1980)
P(論文) A new direction finding technique (abbreviated as DF) for auroral hiss emissions is introduced based on the measurement of time differences of arrival of waves between three spaced observing stations. Two unmanned observatories for VLF hiss were built at positions about 20km south and east from Syowa Station (geomagnetic lat. -69.6°), Antarctica. The VLF signals observed at these two unmanned stations are sent in real time to Syowa Station over 2 GHz wide-band telemetry systems. The arrival time differences of VLF hiss signals between Syowa Station and each unmanned station are automatically determined by cross-correlating the wave forms of the received signals. The arrival directions of hiss emissions are determined by the tripartite observation method. The accuracy of the whole system is about 10°in incident and azimuthal angles. A comparison of the results obtained with those of ground-based auroral data has shown that the arrival directions of auroral hiss correspond well to the bright aurora areas at the ionosphere level and that they change rapidly in accordance with movements of the aurora. departmental bulletin paper